Exploring the Power of Narrative Counseling to Cultivate Meaning in Life of Students - Wijaya, Rasman Sastra; Yusuf, Syamsu; Nurihsan, Juntika; Yustiana, Yusi Riska; Supriatna, Mamat; Wibowo, Mungin Eddy (KONSELOR, 2025)
This study aimed to explore the effectiveness of narrative counseling in enhancing the meaningfulness of life among high school and vocational students in Baubau City, Southeast Sulawesi Province. A quasi-experimental approach with a one-group pretest-posttest design was employed. The participants included 173 students who completed the Meaningfulness of Life Scale and 32 school counselor who had undergone narrative counseling capacity-building training. Through purposive random sampling, 34 school counselor were divided equally into experimental and control groups, with each group comprising 17 school counselor. Each teacher provided narrative counseling to 17 students identified with low to moderately low levels of meaningfulness in life. Narrative counseling sessions were conducted over 3 to 4 sessions by school counselor. The meaningfulness of students' lives was assessed through six indicators: self-understanding, positive attitude change, life purpose, strong commitment, self-direction, and effective social support seeking. Results indicated significant improvements across these indicators. Initially categorized predominantly as low, five indicators improved significantly to fairly high levels, while one indicator reached a moderate category post-intervention. The statistical analysis using the Wilcoxon test yielded a significance value of 0.01 (p < 0.05), confirming a statistically significant difference between pre- and post-intervention outcomes. The Asym.sig (2-tailed) result also confirmed this significance with a value of 0.01. These findings demonstrate the effectiveness of narrative counseling in enhancing students' meaningfulness of life. Consequently, narrative counseling is validated as a valuable strategy for empowering students in high school and vocational settings, significantly fostering their sense of purpose and life direction.